63+5y-20=15y-13-2y

Simple and best practice solution for 63+5y-20=15y-13-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 63+5y-20=15y-13-2y equation:


Simplifying
63 + 5y + -20 = 15y + -13 + -2y

Reorder the terms:
63 + -20 + 5y = 15y + -13 + -2y

Combine like terms: 63 + -20 = 43
43 + 5y = 15y + -13 + -2y

Reorder the terms:
43 + 5y = -13 + 15y + -2y

Combine like terms: 15y + -2y = 13y
43 + 5y = -13 + 13y

Solving
43 + 5y = -13 + 13y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-13y' to each side of the equation.
43 + 5y + -13y = -13 + 13y + -13y

Combine like terms: 5y + -13y = -8y
43 + -8y = -13 + 13y + -13y

Combine like terms: 13y + -13y = 0
43 + -8y = -13 + 0
43 + -8y = -13

Add '-43' to each side of the equation.
43 + -43 + -8y = -13 + -43

Combine like terms: 43 + -43 = 0
0 + -8y = -13 + -43
-8y = -13 + -43

Combine like terms: -13 + -43 = -56
-8y = -56

Divide each side by '-8'.
y = 7

Simplifying
y = 7

See similar equations:

| (7b-7)-2(3b+2)=-6 | | 5y+n=m | | -3.9x-1=-3.5x+3 | | 3/4n-(-16)=28 | | 29xy-3x= | | 2(2x-2)-2(3-4z)=4 | | x=2.857142857+0.1428571429y | | 6k^2-48k=-42 | | -.75x+11=-130 | | 7(4x+8)=-224 | | 13(7c-1)-18=89c+13 | | -p^2+6p+9=0 | | F(X)=(X+2)*2-3 | | 2(3)+y=-12 | | h(2h-1)=91 | | x/-5=1-(-7) | | 2(0)+y=-12 | | 2(-2)+y=-12 | | 1/4x-7/8x=25-55 | | 9y^2+12y+16=0 | | -44+16=-2x+9x | | (3b+4)(7b-1)=0 | | 12a^2+43a+35= | | -47-(-37)=x/2 | | (C-25)(c-81)=0 | | 3*(5-x)=15 | | x+(-1)=4+(-1) | | -4x+5+7x-8+12x-5=-9x+7x+8 | | 12x-19y+3=180 | | 3-5/x-5=5/(x-2)(x-5) | | 5f-6f=2 | | -30+7z=-5(3z+9) |

Equations solver categories